Ethnobotanical Study and Medicinal Plant Bioprospecting in Tamiang Tribal Community, Aceh - Nufus, Cut Azura Izatul; Rasnovi, Saida; Dharma, Wira; Navia, Zidni Ilman; Razi, Nanda Muhammad; Rahmadani, Rahmadani; Anjelia, Via; Meyrita, Meyrita; Najmi, Istafan; Mardudi, Mardudi (Journal of Tropical Ethnobiology, 2024)
Each tribe has a tradition of ethnobotanical plant utilization and management, one of which is the Tamiang tribe. The community realizes the potential of plant utilization, thus creating considerable economic opportunities for bioprospection. This study used the Participatory Rural Appraisal (PRA) method to collect data by actively involving the community. Semi-structured interview techniques were conducted to explore ethnobotanical information from the Tamiang tribe. From the results of the Slovin analysis, 600 respondents with an age range of 35 to 94 years were obtained. Snowball sampling was used to select respondents. Determination of Sub-district locations selected six Sub-districts from 12 Subdistricts by purposive sampling with the largest number of Tamiang Tribe. The results showed that there were 225 species from 74 families used by the Tamiang people in treating various diseases. The most commonly cured diseases are fever, diabetes, and hypertension. Tagetes erecta is the most widely recognized medicinal plant species with a relative citation frequency index of 1.00. At the same time, Andrographis elongata is the most frequently used medicinal plant by the local community with a use value index of 1.00. In addition, local people identified the leaf organ (60.89%) as the most commonly used part of the plant, while decoction (58.20%) was the most popular method of administering traditional medicine. Both species of Andrographis elongata and Moringa oleifera have the potential to treat diabetes and hypertension as seen from the highest ICS value as prospective plants in the utilization and management of medicinal plants, so they can be developed as raw materials for herbal medicine.